THE EFFECT OF PROJECT BASED LEARNING THROUGH ART PERFORMANCE ON STUDENT LEARNING MOTIVATION - Reni Anggraeni (Yayasan Sinergi Widya Nusantara, 2022)
Purpose: Students’ in participating in art learning with art performances need motivation to be able to learn and achieve optimal learning outcomes. One of the learning strategies that can increase learning motivation with the presence of art performances can use Project Based Learning (PBL). The purpose of this study was to examine the effect of Project Based Learning through art performances on student learning motivation. Research methods: The research method uses experimental research methods with a one-shot case study design. Participants in this study were 79 students’ of the PIAUD Department, State Islamic University Sunan Gunung Djati, Bandung. The research instrument used a student learning motivation questionnaire. The data analysis technique used one-sample t test. Findings: The results of the study concluded that there was an effect of PBL through art performances on students' learning motivation. Implications: Using PBL can provide motivation to learn and solve problems in participating in learning.